PENGARUH LOCUS OF CONTROL, PENGALAMAN AUDITOR, DAN ETIKA PROFESIONAL TERHADAP PERILAKU AUDITOR DALAM SITUASI KONFLIK AUDIT - Aprilla Shinta Uli; Amries Rusli Tanjung; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aimed to analyze and to test the influence locus of control, audit experience, and professional ethical to audit behavior in an audit conflict situation. The research has been done in Pekanbaru with auditor respondent working for public accountant company. Retrieval of sample has been using convenience sampling. Number of questionnaires propagated was 80 copies but only 55 copies question returned. The data were analysis for hypothesis tester was done with multiple regression. The result of research the variabel locus of control, audit experience, and professional ethics have significantly influence to audit behavior in an audit conflict situation.Keywords : locus of control, audit experience, professional ethic and audi conflict situation.